Prevalence and clinical features of pityriasis versicolor in children - Rijal, A; Agrawal, S; Bhattarai, S (Health Renaissance, 2012)
Background: Pityriasis versicolor (P.versicolor) is a mild chronic infection of the skin caused by Malassezia yeasts. The disease is more prevalent in teenagers and adults and children are rarely affected. Objective: To study the prevalence and clinical presentation of P.versicolor in children. Methods: All children below 14years of age presenting with hypo pigmented macules were screened for P.versicolor. A 10% KOH examination of skin scrapping was done in all the screened patients. A positive KOH mount showing spores and hyphae were included in the study. The clinical and epidemiological data was noted. Results: The total number of children with hypo pigmented macules was 102 and 58 were positive for PV. In 31.2%patients the lesions were on the face and these patients were below 1 years of age. Most cases presented in the summer months. Oil massage was seen in all patients. Conclusion: Hypo pigmented macules in infants should be screened for PV as this is seen to be quite common. Occlusion due to oil massage may cause PV. DOI: http://dx.doi.org/10.3126/hren.v10i2.6574 Health Renaissance 2012; Vol 10 (No.2); 105-107